Tanulás és versenyképesség regionális megközelítésben - Mohácsi, Márta (Közép-Európai Közlemények, 2014)
The knowledge-based economy not only changes the operation methods of economy, but re-evaluates the human relations and institutions operated by it. With all this, the problem of learning carrying the capacity of knowledge will also be reconsidered. In the European Union the human resource belongs to the factors that influence the competitiveness of the member countries. The carrier, the developer and the utilizer of knowledge capital is the self-fulfilling person with a determined intention for learning. The human factor becomes an economic factor, where the individual’s will, learning inclination and learning ability transforms into competitive edge. The individual and institutional knowledge is created from formal learning and through experience. One of the most important characteristics of knowledge economy is the demand for creative and highly trained employees. Based on these factors, our conception on education and labour market alters. When planning the development processes of education and vocational training, it is practical and justified to consider those regional particularities that appear in the socio-economic environment. This paper seeks the answer to the question of how could individual learning become an economic competitive factor.